Construction of Telemedicine Implementation License Arrangements Application Based in Indonesia - Hadiyantina, Shinta; Supaat, Dina Imam; Sudjati, Xaviera Qatrunnada Djana; Rahmatika, Nur Auliya; Maharani, Tiara (Arena Hukum, 2024)
Health services have become more accessible than ever due to the rise of telemedicine. Among the most popular are application-based telemedicine services, especially those offered by tech companies specialising in teleconsultation. In Indonesia, users are particularly drawn to e-services that partner with healthcare providers, pharmaceutical services or maternity care providers. However, unlike Malaysia and Singapore, which have made significant strides in telemedicine for their communities, Indonesia still faces a legal gap in regulating, implementing, guiding and overseeing telemedicine services—especially those that are application-based and developed by tech companies. This study adopts a juridical-normative approach, analysing Indonesian laws and regulations and comparing them with those in Malaysia and Singapore. Using statutory, conceptual and comparative methods, the study aims to generate specific ideas for implementing regulations to govern the licensing of application-based telemedicine in Indonesia. The findings indicate that Indonesia lacks specific licensing regulations for telemedicine services developed by tech companies. More detailed regulations could be introduced through government regulations that align with the legal framework and ‘beleidsregel’ (policy rules), utilising the discretionary authority of administrative officials to address this regulatory gap. This approach aligns with the legal principle lex semper dabit remedium, meaning ‘the law always provides a remedy’, resonating with the spirit of progressive law in society.